“I Am Not Complaining”: Listening to International Students’ Requests and Complaints as Expressions of Diverse Learning Needs - Torres-Arends, Irene; Jacobsen, Michele (Journal of International Students, 2024)
This study explores the learning needs of international students at a Canadian private university. Through a qualitative content analysis of 580 students’ emails, we identified and examined 819 requests and complaints The analysis highlighted trends about due dates, assignment resubmissions, regrading, and plagiarism issues, leading to the identification of five primary needs: improved internet access and digital literacy support, acknowledgment of cultural differences, assignment design without assumptions, accessible learning management systems, and inclusive learning environments. These findings underline the necessity of empathetic listening to develop strategies that facilitate international students’ transition to Canadian higher education, enhancing their learning experiences. The research suggests innovative approaches for incorporating international students’ perspectives into course and program design, advocating for active engagement with these students to create educational environments that are inclusive and responsive to their unique needs.